Professional Competence of Teachers in History Learning at Senior High School of YPST Porame - Tadoda, Mersy Marselyna; Rore, Idrus; Nugroho, Fajar (Kirana Publisher (KNPub), 2025)
The purpose of this study is to describe the professional competence of history teachers at YPST Porame High School, describe history learning at YPST Porame High School and analyze the important role of teacher professional competence for history learning at YPST Porame High School. Data were collected through observation, interviews, and documentation. Furthermore, the subjects in this study were 4 students of grade X, 4 students of grade XI and 2 history teachers. The data analysis process began with data reduction, data presentation, and drawing conclusions. The results of the study indicate that the professional competence of history teachers at YPST Porame High School has been implemented well, history learning has also been carried out effectively although still limited in terms of facilities but has been running well. From the results of the study it can also be seen that the professional competence of history teachers at YPST Porame High School plays an important role in the success of history learning in the classroom.